A educação escolar na arena do ciberespaço - Oliveira, Alessandro Eleutério de (Universidade Federal de São Carlos, 2013)
The objective of this study is to examine virtual communities dedicated to the School Education site relationships Orkut. Accordingly, we analyze written statements from teachers and students in order to apprehend the ways in which those involved in the teaching-learning perceive each other. That is, how students express themselves about their teachers, as teachers are manifested on students and how teachers and students are manifested on School Education. The rationale for this research is the need of understanding the ways in which the subjects' school experiences are expressed in cyberspace. The examination of the information contained in written statements made effective border methodological content analysis. Thus, the lucubrations are lit mainly by authors of Critical Theory, as Theodor Adorno and Walter Benjamin, by the confluence of the material collected in virtual communities on topics such as disorientation and semi-formation in contemporary as well as your reflexes in Brazilian School Education. Other authors provide important contributions to the construction of this paper are Richard Sennett, Charles Melman and Zygmunt Bauman. To date, the categories derived from the analysis of the data show the existence of largely negative perceptions of teachers on students, and vice versa, from experiences of these subjects in the teaching-learning process. This occurs in a context of reification and fragmentation of socio-cultural, which damages the formative experience. This process hinders the effectiveness of dialogic praxis, which is fundamental to the success of School Education
Keywords: Educação; Experiência formativa; Orkut (Conversação eletrônica); Experience; Orkut; Education; CIENCIAS HUMANAS::EDUCACAO